Resposta :
Resposta:
e) -7
Explicação passo-a-passo:
x - y
19 - 26 = -7
Resposta:
OLÁ
[tex]x - y \\ para \: x = 19.y = 26 \\ substitui \\ x - y \\ 19 - 26 = \\ - 7 \\ letra \: (e) \\ espero \: ter \: ajudado[/tex]
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/d84/6b187f02ca95343cc8aa0412eb5b43de.jpg)
Resposta:
e) -7
Explicação passo-a-passo:
x - y
19 - 26 = -7
Resposta:
OLÁ
[tex]x - y \\ para \: x = 19.y = 26 \\ substitui \\ x - y \\ 19 - 26 = \\ - 7 \\ letra \: (e) \\ espero \: ter \: ajudado[/tex]